AB0854 Body Adiposity Measures and Their Association with Low Back Pain: Result from A Prospective Cohort Study. (15th July 2016) - Hussain, S.M.; Urquhart, D.M.; Wang, Y.; Shaw, J.E.; Magliano, D.J.; Wluka, A.E.; Cicuttini, F.M.
Abstract : Background: Although obesity is associated with low back pain (LBP) prevalence in adults, the mechanism how obesity causes LBP remained unexplored. Since, our current understanding on how obesity causes other joint pain i.e. pain in hand joints suggest that, there must be additional systemic effect of obesity in the pathogenesis of LBP. Thus, clarifying the role of body composition on the risk of LBP is important as it will help in the understanding of likely pathological mechanisms. Objectives: To examine the relationship between adiposity measures and LBP intensity and disability in community based population. Methods: 5, 058 participants (44% men) of the Australian Diabetes, Obesity and Lifestyle Study recruited at 1999–2000 were included. Their body mass index (BMI), waist circumference, and waist-to-hip ratio were obtained from direct anthropometric measurements. The fat mass and percentage fat were estimated from bioelectrical impedance analysis. LBP intensity and disability assessed in 2013–2014 using the Chronic Pain Grade Questionnaire. Results: All the adiposity measures were associated with LBP intensity, independent of fat free mass, for both men and women. The odd ratios (OR) of men for high intensity LBP were BMI OR 1.41 (95% CI 1.17–1.70), waist OR 1.25 (95% CI 1.07–1.46), waist-to-hip ratio OR 1.33 (95% CI 1.03–1.71), percent fat OR 1.45 (95% CI 1.19–1.77), fat mass OR 1.23 (95% CI 1.05–1.44). For women the ORs were - BMI OR 1.39 (95% CI 1.22–1.59), waist OR 1.36 (95% CI 1.22–1.52), waist-to-hip ratio OR 1.49 (95% CI 1.21–1.84), percent fat (10%) OR 1.39 (95% CI 1.22–1.57), fat mass OR 1.27 (95% CI 1.15–1.40). Similarly all adiposity measures were associated with LBP disability. The risk of LBP intensity and disability increased in a linear manner in sex-specific quartiles of all adiposity measures such that the individuals in the highest quartile had the highest risk of developing LBP. Conclusions: All adiposity measures were significantly associated with LBP intensity and disability. This suggests a role for metabolic mechanisms associated with adiposity contribute to the risk of LBP. The rise in the obesity epidemic throughout the world is likely to increase the burden of LBP, as such understanding the mechanism of action will be important in effective prevention of the disease. Disclosure of Interest: None declared